Comparing practices of wrestling in the USA against a global model for integrated development of mass and high-performance sport - Smolianov, P.; Ridpath, B. D.; Morrissette, J. N.; Boucher, C.; Dolmatova, T.; Schoen, C.; Dion, S. (International Journal of Wrestling Science, 2023)
Referencing domestic and global practices, this study provides information on what might be implemented as best practices to advance the sport of wrestling in the USA. The authors utilized the model of integrated elite and mass sport development from past research, which formed the foundation for a questionnaire and interview schedule for US wrestling coaches and administrators to generate a snapshot of perceptions of the current sport system and possibilities for its further development. Survey questions based on more than 200 published sources were validated by six experts including academicians, executives from sport governing bodies, coaches and administrators. To determine the areas for improvement, the questionnaires were completed by 102 coaches. Possible advancements were further identified through semi-structured discussions with 10 wrestling administrators and experts. Results suggest possible enhancements at micro-, meso- and macro-levels of the proposed model for better international performance as well as greater national sport participation.